Evaluasi Kinerja Parkir On Street Di Kota Cilegon Dalam Rangka Peningkatan Retribusi Parkir - Tiara, Jhenia Elva; Virda, Dian; Wisudawanto, Feri (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2024)
This research evaluates the performance of on-street parking in Cilegon City to increase local revenue (Locally- Generated Revenue). Regional autonomy allows local governments to manage resources, including parking fees, which has the potential to increase Locally-Generated Revenue. However, the management of parking fees in Cilegon City is still less than optimal, as evidenced by the low contribution of parking revenue to Locally-Generated Revenue and the failure to achieve the parking fee budget target since 2019. Quantitative research methods are used by analyzing existing conditions, arrangement and parking fees, as well as revenue projections. The survey results show the need for increased parking facilities and better arrangement. Analysis shows a significant increase in income after parking arrangements, especially on Jl. D.I Pandjaitan 1. Even though there has been an increase in income, the effectiveness of the contribution of parking fees to Locally- Generated Revenue is still inconsistent. Analysis of ability to pay (ATP) and willingness to pay (WTP) indicates that existing tariffs are still feasible. Revenue projections after the arrangement show a significant increase, making parking fees a potential source for increasing Cilegon City's Locally-Generated Revenue.